Expression studies of a novel splice site mutation in the LIPH gene identified in a Japanese patient with autosomal recessive woolly hair. Issue 10 (October 2014) - Hayashi, Ryota; Inui, Shigeki; Farooq, Muhammad; Ito, Masaaki; Shimomura, Yutaka
Abstract Autosomal recessive woolly hair (ARWH) is characterized by short and tightly curled scalp hair without any obvious complications. The disease is known to be caused by either lipase H (LIPH) or LPAR6 genes. Proteins encoded by these two genes are closely related to each other in a lipid‐signaling pathway that is believed to play crucial roles in hair follicle development and hair growth. In the Japanese population, most affected individuals with ARWH have been shown to carry two prevalent founder mutations in the LIPH gene, c.736T>A (p.Cys246Ser) and c.742C>A (p.His248Asn), while other LIPH mutations have been occasionally identified. In this study, we analyzed a Japanese patient with ARWH, and identified compound heterozygous mutations in the LIPH gene, c.736T>A (p.Cys246Ser) and c.982+5G>T. The latter one was a novel splice site mutation in intron 7. Expression studies using blood‐derived RNA from the patient detected the LIPH transcript from the c.736T>A mutant allele, but not from the c.982+5G>T mutant allele. Furthermore, in vitro transcription assay in cultured cells showed that the mutation c.982+5G>T caused an aberrant splicing event, leading to a frame‐shift and a premature termination codon (p.Met328Serfs*41). To the best of our knowledge, this is the second splice site mutation in the LIPH gene, and our findings further expand the spectrum of the LIPH mutations underlying ARWH.